Advanced Glycation End-Products Acting as Immunomodulators for Chronic Inflammation, Inflammaging and Carcinogenesis in Patients with Diabetes and Immune-Related Diseases - Shen, Chieh-Yu; Lu, Cheng-Hsun; Cheng, Chiao-Feng; Li, Ko-Jen; Kuo, Yu-Min; Wu, Cheng-Han; Liu, Chin-Hsiu; Hsieh, Song-Chou; Tsai, Chang-Youh; Yu, Chia-Li (Biomedicines, 2024)
Increased production of advanced glycation end products (AGEs) among reducing sugars (glucose, fructose, galactose, or ribose) and amino acids/proteins via non-enzymatic Maillard reaction can be found in lifestyle-related disease (LSRD), metabolic syndrome (MetS), and obesity and immune-related diseases. Increased serum levels of AGEs may induce aging, diabetic complications, cardiovascular diseases (CVD), neurodegenerative diseases (NDD), cancer, and inflamm-aging (inflammation with immunosenescence). The Maillard reaction can also occur among reducing sugars and lipoproteins or DNAs to alter their structure and induce immunogenicity/genotoxicity for carcinogenesis. AGEs, as danger-associated molecular pattern molecules (DAMPs), operate via binding to receptor for AGE (RAGE) or other scavenger receptors on cell surface to activate PI3K-Akt-, P38-MAPK-, ERK1/2-JNK-, and MyD88-induced NF-κB signaling pathways to mediate various pathological effects. Recently, the concept of “inflamm-aging” became more defined, and we have unveiled some interesting findings in relation to it. The purpose of the present review is to dissect the potential molecular basis of inflamm-aging in patients with diabetes and immune-mediated diseases caused by different AGEs.